Luxuries, Necessities, and the Allocation of Time - Lei Fang; Anne Hannusch; Pedro Silos (Institute of Labor Economics (IZA), 2025)
We study consumption and welfare inequality by analyzing how households allocate resources—market expenditures and the value of time—to the production of activities. The share of resources allocated to an activity rises or falls with wages, classifying them into luxuries or necessities, respectively. An estimated model with non-homothetic preferences shows that the rise in consumption inequality between 2004 and 2019 was mostly due to an increase in wage dispersion, while rising prices, especially of leisure luxuries, had a significant negative effect on inequality. The distinction between luxuries and necessities amplifies the counteracting effects of wage and price on inequality.
Keywords: J22; E21; D11; 330; time allocation; consumption expenditures; luxuries; necessities; activity production; inequality